The F-box E3 ubiquitin ligase BAF1 mediates the degradation of the brassinosteroid-activated transcription factor BES1 through selective autophagy in Arabidopsis. Issue 11 (26th August 2021) - Wang, Ping; Nolan, Trevor M; Clark, Natalie M; Jiang, Hao; Montes-Serey, Christian; Guo, Hongqing; Bassham, Diane C; Walley, Justin W; Yin, Yanhai
Abstract : During sucrose starvation, BAF1-mediated degradation of the transcription factor BES1 via selective autophagy inhibits brassinosteroid signaling. Abstract: Brassinosteroids (BRs) regulate plant growth, development, and stress responses by activating the core transcription factor BRI1-EMS-SUPPRESSOR1 (BES1), whose degradation occurs through the proteasome and autophagy pathways. The E3 ubiquitin ligase(s) that modify BES1 for autophagy-mediated degradation remain to be fully defined. Here, we identified an F-box family E3 ubiquitin ligase named BES1-ASSOCIATED F-BOX1 (BAF1) in Arabidopsis thaliana . BAF1 interacts with BES1 and mediates its ubiquitination and degradation. Our genetic data demonstrated that BAF1 inhibits BR signaling in a BES1-dependent manner. Moreover, BAF1 targets BES1 for autophagic degradation in a selective manner. BAF1-triggered selective autophagy of BES1 depends on the ubiquitin binding receptor DOMINANT SUPPRESSOR OF KAR2 (DSK2). Sucrose starvation-induced selective autophagy of BES1, but not bulk autophagy, was significantly compromised in baf1 mutant and BAF1-ΔF (BAF1 F-box decoy) overexpression plants, but clearly increased by BAF1 overexpression. The baf1 and BAF1-ΔF overexpression plants had increased BR-regulated growth but were sensitive to long-term sucrose starvation, while BAF1 overexpression plants had decreased BR-regulated growth but were highly tolerant of sucrose starvation. Our results not only established BAF1 as an E3 ubiquitin ligase that targets BES1 for degradation through selective autophagy pathway, but also revealed a mechanism for plants to reduce growth during sucrose starvation.